2023
DOI: 10.3390/molecules28041591
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel for the Controlled Delivery of Bioactive Components from Extracts of Eupatorium glutinosum Lam. Leaves

Abstract: This research reported a hydrogel loaded with the ethanolic and methanolic extracts of Eupatorium glutinosum Lam. The E. glutinosum extracts were characterized by phytochemical screening, Fourier-transform infrared spectroscopy (FTIR), thin-layer chromatography (TLC), and UV/Vis profile identification. This research also evaluated the pharmacological activity of the extracts using antimicrobial, antioxidant, and anti-inflammatory assays prior to polymeric encapsulation. Results indicate that extracts inhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Furthermore, isolated apigenin was effective against P. aeruginosa, K. pneumoniae, S. Typhimurium, P. mirabilis, and K. aerogenes. Similarly, the synergistic antibacterial effect of apigenin, together with beta-lactam antibiotics, was also observed against MRSA [45]. In addition, apigenin and ceftazidime also exhibited a synergistic antibacterial effect against ceftazidime-resistant E. cloacae [103].…”
Section: Honey and Propolismentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, isolated apigenin was effective against P. aeruginosa, K. pneumoniae, S. Typhimurium, P. mirabilis, and K. aerogenes. Similarly, the synergistic antibacterial effect of apigenin, together with beta-lactam antibiotics, was also observed against MRSA [45]. In addition, apigenin and ceftazidime also exhibited a synergistic antibacterial effect against ceftazidime-resistant E. cloacae [103].…”
Section: Honey and Propolismentioning
confidence: 76%
“…Historically, plant extracts have been used to treat several bacterial infections in medicine [43]. Several techniques have allowed the extraction and identification of bioactive compounds to recognize the mechanism of action that causes bacteriostatic effects [44,45]. Plant extracts which have antibacterial effects can be obtained from roots, fruits, flowers, stems, leaves, and seeds.…”
Section: Plant Extractsmentioning
confidence: 99%
“…Meanwhile, time‐kill assay is viable technique useful to characterize the antimicrobial activity during time evidencing the dynamic interaction between the optimal concentration of the antimicrobial agent and the microbial pathogens (Balouiri et al., 2016). Therefore, the most suitable approach to characterize the antimicrobial activity of honey samples should be initiated by screening the best candidates by agar disc‐diffusion or overlay assay and a further evaluation of the obtained candidates should also be performed through broth microdilution and time‐kill assays (Cabezas‐Mera et al., 2023; Zamora‐Mendoza et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The data of this study indicated that bilberry leaf extract compounds maintained the tonicity and balance of the erythrocyte membrane and thereby prevented its lysis. Bioactives of the plant extracts, including tannins, flavonoids, coumarins, etc., can have an important role in decreasing the plasma membrane stress caused by high temperature or hypotonic solution [ 129 ]. Bonarska-Kujawa et al [ 130 ] reported that chlorogenic acid molecules are positioned mainly in the outer part of the erythrocyte membrane (hydrophilic region) and do not induce lysis or osmolality changes, preventing the diffusion of free radicals into the membrane interior.…”
Section: Discussionmentioning
confidence: 99%